Measles Immune Suppression: Functional Impairment or Numbers Game? - de Vries, Rory D.; de Swart, Rik L. (PLoS pathogens, 2014)
Resolution of MV infection is associated with increased lymphoproliferation [8], [24] and enlargement of lymph nodes [13]. [...]the immune system efficiently restricts MV replication and clears MV-infected cells. Do Dendritic Dells Play a Crucial Role? DC subsets have been shown susceptible to MV infection in vitro [15]-[17] and in nonhuman primates in vivo [11], [19]. [...]it is likely that infection, depletion, or functional modulation of DCs contributes to measles-associated immune suppression.